Pengaruh Kualitas Sistem, Kualitas Informasi, dan Kualitas Layanan terhadap Kepuasan Pengguna pada Aplikasi Tangerang Live Menggunakan Metode Delone dan Mclean - Shifa Nasyiatun Nasuha; Qori Halimatul Hidayah (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2026)
Tangerang City, as one of the cities implementing the Smart City concept, provides broader opportunities for the community to participate in and monitor urban development. One of the digital innovations introduced is the Tangerang Live Application, a public service application designed to meet various needs of the residents of Tangerang City. This study aims to identify the factors that influence user satisfaction and the impact of using the Tangerang Live Application. The research employs a quantitative approach using the DeLone & McLean method, which focuses on three main dimensions: system quality, information quality, and service quality. The population in this study consists of users of the Tangerang Live Application, with a sample size of 100 respondents obtained through a simple random sampling technique. Data collection was carried out through the distribution of questionnaires. Data analysis was conducted using multiple linear regression analysis with the assistance of IBM SPSS (Statistical Package for the Social Sciences) software. The results of this study are expected to provide a clear picture of the influence of system quality, information quality, and service quality on user satisfaction, and serve as a reference for the future development of more effective public service applications.